2010
DOI: 10.3233/thc-2010-0580
|View full text |Cite
|
Sign up to set email alerts
|

Robotized access to the medullary cavity for intramedullary nailing of the femur

Abstract: Introduction: The insertion site for an antegrade femoral intramedullary nail in the treatment of a femoral shaft fracture has traditionally been performed using a free-hand technique. An inappropriate starting point can result in suboptimal nail insertion leading to malreduction, or iatrogenic fracture. Furthermore, repeated attempts to establishthe optimal starting point cancause additional soft tissue trauma and radiation exposure. In the following study we compared a robot-guided technique with the standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…As part of a long‐term focus on developing a fully‐robotic platform for long‐bone fracture treatment, we have performed specific tests of each part of the procedure . In this instance, we aimed to test a robotic implementation for distal locking, which is widely recognized as one of the most technically challenging steps of the intramedullary nailing procedure .…”
Section: Discussionmentioning
confidence: 99%
“…As part of a long‐term focus on developing a fully‐robotic platform for long‐bone fracture treatment, we have performed specific tests of each part of the procedure . In this instance, we aimed to test a robotic implementation for distal locking, which is widely recognized as one of the most technically challenging steps of the intramedullary nailing procedure .…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to improve outcomes after intramedullary nailing of femur fractures, we have worked on developing a comprehensive roboticassisted operative technique. [6][7][8][9][10]13,14,[17][18][19][20][21][22][23] We have previously shown that surgeon-performed telemanipulated fracture reduction is effective and accurate for simple fracture types. To further improve the accuracy of more complex fractures, we have worked on automated fracture reduction algorithms that are able to rearrange the fracture fragments into their optimal position and plan an efficient and minimally traumatic fracture reduction path.…”
Section: Discussionmentioning
confidence: 99%
“…The continued development of advanced three‐dimensional (3D) imaging techniques, computer navigation and surgical robotics has made it possible to design methods aimed at improving the intramedullary nailing techniques. We have previously described several components of a computer‐assisted robotic framework for intramedullary nailing of the femur, including the successful implementation of telemanipulated 2D and 3D fracture reduction . These techniques are highly accurate for simple fractures, but the effectiveness of the procedure decreases in complex fractures with multiple small fragments and without a clear connection between the main ends of the femur segments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozwald et al . developed a robotic technique for improving the entry‐point access of antegrade femoral nailing . Lei et al .…”
Section: Introductionmentioning
confidence: 99%